Alkaline gallium nitride polishing solution based on Fenton reaction and preparation method thereof
By using iron-based ionic complexes to catalyze hydrogen peroxide in an alkaline environment, the application scope of Fenton reaction is broadened, and the problems of low oxidation efficiency and limited application range in the prior art have been solved, and efficient and environmentally friendly gallium nitride polishing effect have been achieved.
Patent Information
- Application Number
- CN202411601811.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The prior art has low oxidation efficiency in the field of gallium nitride polishing, deposition of trivalent iron ions after reaction, and can only be carried out in an acidic environment, which limits its application scope.
By using iron-based ion complexes to catalyze hydrogen peroxide in an alkaline environment, the scope of application of Fenton's reaction is broadened, and the conversion of trivalent ferrous ions to ferrous ions is promoted through stabilizers, thereby extending the effective time of the polishing liquid.
It realizes efficient gallium nitride polishing under alkaline conditions, improves polishing efficiency and use range, and obtains good polishing surface quality, while avoiding equipment corrosion and environmental pollution.
Smart Images

Figure CN119709020A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical mechanical polishing and relates to an alkaline gallium nitride polishing liquid based on Fenton reaction and a preparation method thereof. Background Art
[0002] Gallium nitride (GaN) is a compound semiconductor material composed of nitrogen and gallium, and is a third-generation semiconductor material. Because of its wide bandgap characteristics, it is also called a wide bandgap semiconductor material. Gallium nitride materials have the characteristics of large bandgap width, high breakdown electric field, high thermal conductivity, high electron saturation rate, and strong radiation resistance. Therefore, semiconductor devices made of GaN materials have the advantages of high voltage resistance, high temperature resistance, low power consumption, small size, and light weight compared to traditional silicon-based devices. At present, gallium nitride has gradually entered the stage of large-scale application. In the field of power devices, gallium nitride diodes, MOSFETs, and optoelectronic devices LEDs have begun commercial applications, and they also have broad application potential in detection devices.
[0003] The processing precision of GaN substrates directly affects device performance. Epitaxy and device applications have extremely stringent requirements on the surface quality of GaN substrates. GaN has high hardness, high brittleness, and stable chemical properties, and traditional processing methods are difficult to meet the processing requirements. Limited by processing technology, the processing efficiency of GaN substrates with high surface quality is currently extremely low.
[0004] The processing of gallium nitride single crystals is mainly divided into slicing, grinding and polishing, among which polishing is the most critical link to determine the surface quality. The polishing process of gallium nitride wafers can be divided into rough polishing and fine polishing. Rough polishing is mechanical polishing, the purpose of which is to improve the processing efficiency of polishing. The key research direction of mechanical polishing of gallium nitride single crystal substrates is to optimize process parameters, improve the surface roughness of wafers, and increase material removal rate. Chemical mechanical polishing is the most widely used gallium nitride fine polishing technology. Through the synergistic effect of chemical corrosion and mechanical wear, the material surface is removed and flattened. Its basic principle is that the gallium nitride wafer undergoes oxidation reaction under the action of polishing liquid, and the resulting softened layer is relatively easy to remove under the mechanical action of abrasive particles. Fenton reaction is a common chemical oxidation system. The mechanism of the Fenton reaction is that ferrous ions catalyze hydrogen peroxide to produce hydroxyl radicals to oxidize the wafer, forming a soft layer that is easy to remove. However, there are many problems with the Fenton reaction, such as low oxidation efficiency, deposition of trivalent iron ions after the reaction, and it can only be carried out in an acidic environment. At present, many studies are also actively expanding the application scope of Fenton reaction in the field of wafer processing, but it is not common in the field of gallium nitride polishing. Currently, there are few gallium nitride wafer polishing liquids without auxiliary means. Chinese patent CN 112126357 B discloses a polishing liquid that uses catalyst adsorption to assist in polishing gallium nitride, but it can only have a good effect under acidic conditions. Chinese patent CN 117551393 A discloses a gallium nitride polishing liquid for electrochemical assisted polishing, which can only be used for electrochemical assisted polishing, which is limited in application and requires external equipment. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides an alkaline gallium nitride polishing liquid based on the Fenton reaction and a preparation method thereof. The iron ions are complexed by a complexing agent, and with the assistance of a stabilizer, the iron ions can circulate and catalyze hydrogen peroxide to continuously produce hydroxyl oxide gallium nitride to form a soft layer, which is then removed by the mechanical action of an abrasive.
[0006] A Fenton reaction-based alkaline gallium nitride polishing liquid comprises components of hydrogen peroxide, silicon dioxide abrasive, sodium bicarbonate, iron salt, dispersant, stabilizer, complexing agent and deionized water, wherein the weight percentage of each component is: 5-30wt% hydrogen peroxide with a mass concentration of 30%, 0.01-15wt% silicon dioxide abrasive, 0.01-1wt% sodium bicarbonate, 0.1-8wt% iron salt, 0.01-2wt% dispersant, 0.01-2wt% stabilizer, 0.1-8wt% complexing agent, and the balance is deionized water.
[0007] Preferably, the components of the polishing liquid are: 5-15wt% hydrogen peroxide with a mass concentration of 30%, 0.01-2wt% silica abrasive, 0.01-1 wt% sodium bicarbonate, 0.1-1 wt% iron salt, 0.05-1wt% dispersant, 0.5-1 wt% stabilizer, 0.1-2 wt% complexing agent, and the balance is deionized water.
[0008] Preferably, the dispersant is any one of surfactants such as hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, Tween, polyethylene glycol octylphenyl ether, etc.
[0009] Preferably, the stabilizer is any one of ether, hydroxylamine, zinc nitrate and zinc sulfate.
[0010] Preferably, the complexing agent is any one of ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid, hydroxyethylethylenediaminetriacetic acid, and sodium pyrophosphate.
[0011] Preferably, the iron salt is ferrous sulfate.
[0012] The present invention also provides a method for preparing the above-mentioned polishing liquid, comprising the following steps: adding sodium bicarbonate to deionized water and stirring until it is completely dissolved; adding a complexing agent, an iron salt, a stabilizer and a dispersant in sequence, stirring and dissolving, adding a silicon dioxide abrasive and stirring and dispersing for 30-60 minutes, and finally adding hydrogen peroxide with a mass concentration of 30% to obtain an alkaline gallium nitride polishing liquid.
[0013] Beneficial effects of the present invention: Compared with the prior art, the present invention is more convenient to operate without the need for additional auxiliary equipment. Hydrogen peroxide is catalyzed by an iron-based ion complex. The application scope of the Fenton reaction is broadened to alkaline conditions. The stabilizer can promote the conversion of trivalent iron ions into ferrous ions, enhance the catalytic effect of ferrous ions, and extend the effective duration of the polishing liquid. The purpose is to improve the polishing efficiency and application scope of the polishing liquid and obtain good polishing surface quality of the wafer. In addition, the polishing liquid does not corrode processing equipment, does not pollute the environment, has low cost, and can be stably stored for a long time. Therefore, the polishing liquid has the characteristics of stability, high efficiency, simple operation, and a wide range of application environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is an atomic force microscope (AFM) image after a gallium nitride substrate wafer is polished using the polishing liquid of Example 1 of the present invention; Figure 2 The graphs of the hydroxyl concentrations of Example 1 and Comparative Example 2 changing with time are shown in FIG. DETAILED DESCRIPTION
[0015] The following will be combined with the accompanying drawings of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] Example 1 A method for preparing alkaline gallium nitride polishing liquid based on Fenton reaction Take 935g of deionized water, add 5g of sodium bicarbonate, and stir until completely dissolved; then add 5g of EDTA, 5g of ferrous sulfate, 10g of hydroxylamine and 10g of hexadecyltrimethylammonium bromide, stir to dissolve, add 20g of silica abrasive Powder-A and stir and disperse for 30 minutes, add 100g of hydrogen peroxide with a mass concentration of 30% to obtain an alkaline gallium nitride polishing liquid; the silica abrasive Powder-A has a diameter D = 30-60nm and a specific surface area of 21.95m 2 / g, atomic force microscopy (AFM) was used to observe the surface roughness of the samples. Figure 1 shown.
[0017] Example 2 A method for preparing alkaline gallium nitride polishing liquid based on Fenton reaction Take 935g of deionized water, add 5g of sodium bicarbonate, and stir until completely dissolved; then add 5g of diethylenetriaminepentaacetic acid, 5g of ferrous sulfate, 10g of ether and 10g of sodium dodecylbenzenesulfonate, stir to dissolve, add 10g of silica abrasive Powder-A and stir and disperse for 35 minutes, add 400g of hydrogen peroxide with a mass concentration of 30% to obtain the alkaline gallium nitride polishing liquid; the silica abrasive Powder-A has a diameter D = 30-60nm and a specific surface area of 21.95m 2 / g.
[0018] Example 3 A method for preparing alkaline gallium nitride polishing liquid based on Fenton reaction Take 935g of deionized water, add 6g of sodium bicarbonate, and stir until completely dissolved; then add 15g of hydroxyethylethylenediaminetriacetic acid, 6g of ferrous sulfate, 10g of zinc nitrate and 10g of hexadecyltrimethylammonium bromide, stir to dissolve, add 40g of silica abrasive Powder-B and stir and disperse for 40 minutes, add 100g of hydrogen peroxide with a mass concentration of 30% to obtain an alkaline gallium nitride polishing liquid; the silica abrasive Powder-B has a diameter D = 90-100nm and a specific surface area of 18.32m 2 / g.
[0019] Example 4 A method for preparing alkaline gallium nitride polishing liquid based on Fenton reaction Take 935g of deionized water, add 6g of sodium bicarbonate, and stir until completely dissolved; then add 10g of EDTA, 5g of ferrous sulfate, 10g of zinc sulfate and 15g of sodium dodecyl sulfate, stir to dissolve, add 40g of silica abrasive Powder-C and stir and disperse for 45 minutes, add 200g of hydrogen peroxide with a mass concentration of 30% to obtain an alkaline gallium nitride polishing liquid; the silica abrasive Powder-C has a diameter D = 110-120nm and a specific surface area of 16.19m 2 / g.
[0020] Example 5 A method for preparing alkaline gallium nitride polishing liquid based on Fenton reaction Take 935g of deionized water, add 5g of sodium bicarbonate, and stir until completely dissolved; then add 10g of hydroxyethylethylenediaminetriacetic acid, 10g of ferrous sulfate, 5g of ether and 10g of polyethylene glycol octylphenyl ether, stir to dissolve, add 50g of silica abrasive Powder-B and stir and disperse for 50 minutes, add 300g of hydrogen peroxide with a mass concentration of 30% to obtain an alkaline gallium nitride polishing liquid; the silica abrasive Powder-B has a diameter D = 90-100nm and a specific surface area of 18.32m 2 / g.
[0021] Example 6 A method for preparing alkaline gallium nitride polishing liquid based on Fenton reaction Take 935g of deionized water, add 5g of sodium bicarbonate, and stir until completely dissolved; then add 5g of sodium pyrophosphate, 5g of ferrous sulfate, 10g of hydroxylamine and 5g of Tween, stir to dissolve, add 100g of silica abrasive Powder-C and stir and disperse for 60 minutes, add 400g of hydrogen peroxide with a mass concentration of 30% to obtain an alkaline gallium nitride polishing liquid; the silica abrasive Powder-C has a diameter D = 110-120nm and a specific surface area of 16.19m 2 / g.
[0022] Comparative Example 1 The remaining operating steps are the same as those in Example 1, except that the contents of the components in the polishing liquid are: 935g deionized water, 5g sodium bicarbonate, 5g ferrous sulfate and 100g hydrogen peroxide with a mass concentration of 30%, which is stirred evenly and the pH of the liquid is 9.8.
[0023] Comparative Example 2 The remaining operating steps are the same as those in Example 1, except that the contents of the components in the polishing liquid are: 935g deionized water, 5g sodium bicarbonate, 5g EDTA, 5g ferrous sulfate and 100g hydrogen peroxide with a mass concentration of 30%, which is stirred evenly and the pH of the liquid is 9.8.
[0024] Test Example 1 Polishing experiments were carried out on the polishing liquids obtained in Examples 1-6 and Comparative Examples 1-2.
[0025] This polishing experiment uses a 2-inch GaN substrate and polishes the N side. The polishing parameters are set as follows: the polishing pressure is 300g / cm 2 ; The polishing pad speed is 50rpm; The polishing head speed is 40rpm; The polishing liquid flow rate is 15mL / min; The polishing time is 60min. After each polishing, the polishing pad is replaced, and the polished substrate is ultrasonically cleaned in the cleaning liquid for 10 minutes and then blown dry with nitrogen. The results are shown in Table 1.
[0026] The polishing removal rate (MRR) calculation formula is: MRR = Δm / ρS, where Δm is the quality difference of the substrate wafer before and after polishing; ρ is the density of the substrate wafer; and S is the substrate area.
[0027] Surface defects were detected by visual inspection and defect surface detection lamp; surface roughness was detected by atomic force microscopy (AFM).
[0028] Table 1 Polishing test results of Examples 1-6 and Comparative Examples 1-2
[0029] As can be seen from Table 1, compared with Example 1, no complexing agent and stabilizer are added in Comparative Example 1. Ferrous ions cannot stably exist in an alkaline environment without a complexing agent. Iron hydroxide precipitates are formed. The precipitates seriously damage the surface of the wafer during polishing, so the processing quality is poor.
[0030] As can be seen from Table 1, no stabilizer was added to Comparative Example 2 compared with Example 1. There was a certain polishing effect. However, without the stabilizer, the non-catalytic trivalent iron was reduced back to the catalytic divalent iron. As the processing time increased, the oxidation effect weakened. The mechanical action of the abrasive was too strong, resulting in poor processing quality.
[0031] Test Example 2 The alkaline gallium nitride polishing liquids of Example 1 and Comparative Example 2 were taken in equal amounts to test the hydroxyl concentration.
[0032] Hydroxyl is the main free radical that plays an oxidizing role in the Fenton reaction. Testing its concentration can intuitively reflect the duration of the polishing liquid. The hydroxyl concentration test uses the common spectrophotometric method. The principle is that salicylic acid can capture hydroxyl radicals to generate 2,3-dihydroxybenzoic acid and 2,5-dihydroxybenzoic acid with characteristic absorption between wavelengths of 490-550nm. Fitting the characteristic peak can reflect the hydroxyl concentration. Take 3 ml of the alkaline gallium nitride polishing liquid of Example 1 and Comparative Example 2 and put them into two quartz cuvettes respectively. Then add 2 ml of salicylic acid-ethanol indicator solution to each to start the reaction. Use a UV-visible scanning spectrophotometer for testing. Test the scanning curves for 15 minutes, 30 minutes, 45 minutes, and 60 minutes of reaction respectively. After the test, the characteristic absorption peak of 490-550nm of the obtained curve is fitted and integrated to obtain a line graph of the hydroxyl concentration changes of Example 1 and Comparative Example 2, as shown in Figure 2 As shown. It can be seen that the hydroxyl concentration of Example 1 is significantly greater than that of Comparative Example 2 after 30 minutes. The only difference between the alkaline gallium nitride polishing liquids of Example 1 and Comparative Example 2 is the use of a stabilizer. Therefore, it can be further confirmed that the presence of a stabilizer can promote the conversion of trivalent iron ions into ferrous ions, enhance the catalytic effect of ferrous ions, and extend the effective duration of the polishing liquid.
[0033] Based on Table 1 and the results of the examples, the present invention effectively overcomes various shortcomings in the prior art, and the alkaline gallium nitride polishing liquid based on the Fenton reaction developed by the present invention has high industrial utilization value.
[0034] The above describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
Claims
1. An alkaline gallium nitride polishing liquid based on Fenton reaction, characterized in that: The alkaline gallium nitride polishing liquid comprises hydrogen peroxide, silicon dioxide abrasive, sodium bicarbonate, iron salt, dispersant, stabilizer, complexing agent and deionized water, wherein the weight percentage of each component is: 5-30wt% hydrogen peroxide with a mass concentration of 30%, 0.01-15wt% silicon dioxide abrasive, 0.01-1 wt% sodium bicarbonate, 0.1-8wt% iron salt, 0.01-2wt% dispersant, 0.01-2wt% stabilizer, 0.1-8wt% complexing agent, and the balance is deionized water.
2. The alkaline gallium nitride polishing liquid according to claim 1, characterized in that: The weight percentages of the components in the alkaline gallium nitride polishing liquid are as follows: 5-15wt% hydrogen peroxide with a mass concentration of 30%, 0.01-2wt% silicon dioxide abrasive, 0.01-1 wt% sodium bicarbonate, 0.1-1 wt% iron salt, 0.05-1wt% dispersant, 0.5-1 wt% stabilizer, 0.1-2 wt% complexing agent, and the balance is deionized water.
3. The alkaline gallium nitride polishing liquid according to claim 1, characterized in that: The dispersant is any one of surfactants such as hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, Tween, polyethylene glycol octylphenyl ether, etc.
4. The alkaline gallium nitride polishing liquid according to claim 1, characterized in that: The stabilizer is any one of ether, hydroxylamine, zinc nitrate and zinc sulfate.
5. The alkaline gallium nitride polishing liquid according to claim 1, characterized in that: The complexing agent is any one of ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid, hydroxyethylethylenediaminetriacetic acid, and sodium pyrophosphate.
6. The alkaline gallium nitride polishing liquid according to claim 1, characterized in that: The iron salt is ferrous sulfate.
7. The method for preparing the alkaline gallium nitride polishing liquid according to any one of claims 1 to 6, characterized in that: The preparation steps of the polishing liquid are as follows: adding sodium bicarbonate to deionized water and stirring until it is completely dissolved; adding a complexing agent, an iron salt, a stabilizer and a dispersant in sequence and stirring to dissolve; adding silicon dioxide abrasive and stirring and dispersing for 30-60 minutes; and finally adding hydrogen peroxide with a mass concentration of 30% to obtain an alkaline gallium nitride polishing liquid.
Citation Information
Patent Citations
A polishing solution for gallium nitride substrate material
CN112126357B
Green polishing solution for gallium nitride wafer
CN117551393A
Polishing solution for gallium nitride substrate material
CN112126357A
Chemico-mechanical polishing solution for gallium nitride by combining soft and hard mixed abrasive with photocatalysis and Fenton reaction and polishing method thereof
CN115011256A
Iron-containing silicon carbide substrate polishing solution
CN118562392A
Cited By
Polishing process for metal part with anodic oxide film
CN121104807A